Highly‐Adaptable Optothermal Nanotweezers for Trapping, Sorting, and Assembling across Diverse Nanoparticles - Chen, Jiajie; Zhou, Jianxing; Peng, Yuhang; Dai, Xiaoqi; Tan, Yan; Zhong, Yili; Li, Tianzhong; Zou, Yanhua; Hu, Rui; Cui, Ximin; Ho, Ho‐Pui; Gao, Bruce Zhi; et al. (Advanced materials (Weinheim), 2024)
Optical manipulation of various kinds of nanoparticles is vital in biomedical engineering. However, classical optical approaches demand higher laser power and are constrained by diffraction limits, necessitating tailored trapping schemes for specific nanoparticles. They lack a universal and biocompatible tool to manipulate nanoparticles of diverse sizes, charges, and materials. Through precise modulation of diffusiophoresis and thermo‐osmotic flows in the boundary layer of an optothermal‐responsive gold film, highly adaptable optothermal nanotweezers (HAONTs) capable of manipulating a single nanoparticle as small as sub‐10 nm are designed. Additionally, a novel optothermal doughnut‐shaped vortex (DSV) trapping strategy is introduced, enabling a new mode of physical interaction between cells and nanoparticles. Furthermore, this versatile approach allows for the manipulation of nanoparticles in organic, inorganic, and biological forms. It also offers versatile function modes such as trapping, sorting, and assembling of nanoparticles. It is believed that this approach holds the potential to be a valuable tool in fields such as synthetic biology, optofluidics, nanophotonics, and colloidal science. Highly‐adaptable optothermal nanotweezer (HAONT) is a universal optothermal manipulation scheme with sub‐10 nm precision, enabling trapping, sorting, assembling, and novel doughnut‐shaped vortex trapping across diverse nanoparticles. Its versatility expands its functionality to a broad spectrum of nanoparticles, making it a useful tool for versatile nano‐fabrication across various materials, charges, shapes, sizes, and beyond.